Concepción, diseño y validación de un sistema para la estimación de la fuerza en miembro superior durante movimiento de flexión (2020)
There are different rehabilitation and physiotherapy or training tools on the market, but their costs are often quite high, making accessibility difficult for different health professionals who are involved in estimating strength values during muscle activities. Among these you can find tools such as isokinetic machines, ranging from dynamometers to measure the force made in the grip, to supremely sophisticated devices that allow therapy and training sessions for subjects who require these highly required in the field of physiotherapy and for high level athletes. What makes the implementation of these devices of great relevance because it allows to identify strength values that are required to carry out different activities required in the daily life of the human being, so the loss or deficiency of this capacity prevents quality of life in many people, mainly the risk in older adults who are the most vulnerable. \\ The present project proposes the conception, design and validation of a device to estimate the force values during the flexing movement, from a load cell, its respective calibration and conditioning with the HX711 module, in addition to allowing easy handling for the user. from a graphical interface and allow the data to carry out the respective tests that demonstrate that the device is functional from the Matlab and Arduino software. The graphical interface facilitates the handling of the device for the user, it has three modes of operation such as the child of the calibration to visualize the linear adjustment graph, the operation mode to detect the force which allows to visualize and store the data affected by the perform elbow flexion and therapy mode of operation that allows the user to perform specific therapies, all done with the Matlab guide command. Once you have obtained the force values made on the test subjects, obtain force values similar to those consulted in the literature, in addition to carrying out different tests to determine the device that works with optimal conditions. During the course of the project, the use of other devices will be considered, which would allow an improvement in the activation of these force values, in addition to an improvement in the device being conceived in a way that allows a broader movement, in addition to the validation results were the optimal ones to be able to implement this device in the biomechanics laboratory.